ISSUES OF MODELING THE FORMATION OF TRAINING AND PROFESSIONAL SUCCESS OF FUTURE OFFICERS OF THE NATIONAL GUARD TROOPS OF THE RUSSIAN FEDERATION - Anatoly V. Dubinin; Petr Yu. Naumov (Russian Journal of Education and Psychology, 2022)
Relevance. Modeling and application of models as a special method of cognition has gained recognition in many fields of science. This method is also important in pedagogical science, which indicates its constructiveness. At present, a large number of studies have been conducted on the problems of modeling, revealing the use of models and methods for modeling educational activities in military educational organizations of higher education of the troops of the National Guard of the Russian Federation.